2017
DOI: 10.1002/jctb.5282
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of glycerol with in situH2 formation over Pt catalysts supported on Fe modified Al2O3: effect of Fe loading

Abstract: BACKGROUND: Glycerol hydrodeoxygenation to 1,2-propanediol is a reaction of commercial and environmental significance. However, the need for hydrogen supply is a main drawback of the process. This study aims at the development of effective catalysts for glycerol hydrodeoxygenation with in situ H 2 formed. Pt/Al 2 O 3 and Pt/Fe 2 O 3 -Al 2 O 3 catalysts with different Fe/Pt ratios were synthesized and evaluated. N 2 physisorption, XRD, TPR-H 2 , TGA and DRIFTS-CO characterization techniques were used. Main focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…However, more experiments are needed to explore the conversion % in a temperature higher than 443 K. However, H2 pressure optimization showed that the best MIBK conversion was achieved at 10 atm, while at H2 pressure = 15 the obtained conversion decreased. This can be explained by to the blocking of the active sites at high H2 pressure, as reported by Lemonidou and co-workers [24], and Holles and co-workers [25].…”
Section: Discussionsupporting
confidence: 53%
“…However, more experiments are needed to explore the conversion % in a temperature higher than 443 K. However, H2 pressure optimization showed that the best MIBK conversion was achieved at 10 atm, while at H2 pressure = 15 the obtained conversion decreased. This can be explained by to the blocking of the active sites at high H2 pressure, as reported by Lemonidou and co-workers [24], and Holles and co-workers [25].…”
Section: Discussionsupporting
confidence: 53%
“…The role of Fe 3+ species as a promoter for bifunctional catalysts is largely unexplored. In another study, Lemonidou and co‐workers studied the influence of Fe 3+ loading on the surface acidity of an Al 2 O 3 support and promotional effects for CTH‐II of glycerol in the presence of Pt catalysts . Strong interactions between Fe 2 O 3 and Al 2 O 3 phases lower the crystal size of the latter species.…”
Section: Case Study A: Polyol Conversionmentioning
confidence: 99%
“…In another study,L emonidou and co-workerss tudied the influence of Fe 3 + loading on the surface acidity of an Al 2 O 3 support and promotional effects forC TH-II of glycerol in the presence of Pt catalysts. [46] Strong interactions between Fe 2 O 3 and Al 2 O 3 phases lower the crystal size of the latter species. With increasing Fe loading, characterization by means of diffuse reflectance IR Fourier transform spectroscopy (DRIFTS) indicates that the electron density of Pt increases, although the effect of such electron-transfer behavior from Fe to Pt of ab ifunctional nature is still not correlated with experimental data in this work.…”
Section: Cth-i Routementioning
confidence: 99%
“…This issue of the Journal of Chemical Technology and Biotechnology (JCTB) includes 8 research articles that deal with catalytic oxidation, hydrodeoxygenation, oxidative esterification, epoxidation/ring‐opening/polymerisation and hydrogenation of bio‐sourced reactants.…”
mentioning
confidence: 99%
“…Iron as a promotor in glycerol hydrodeoxygenation (to 1,2‐propanediol) over Pt/Al 2 O 3 was considered by Yfanti et al . . Incorporation of Fe served to increase catalytic activity, which is linked to Fe→Pt electron transfer.…”
mentioning
confidence: 99%